Uncover your message : the 3-step process for presenting your ideas effectively and persuasively, globally and locally - Lipschutz, Natsuyo N. (New York, NY : Routledge, 2025)
Written by a non-native English-speaking professional speaker with over 20 years of international consulting experience, this book lays out a step-by-step process to improve cross-cultural communication skills and achieve a strong global presence. Every year, organizations lose money, time, and people due to poor or inefficient cross-cultural communication - and this can be as easily between departments or individuals within an organization as across oceans. To tackle this widespread problem, Natsuyo N. Lipschutz developed the 3-step process she calls the 3As (Acknowledge, Analyze, Adapt), using a unique multilayered approach: cross-culture logical thinking storytelling. Using the 3As process, readers will improve their awareness of cultural differences and learn analytical and logical thinking skills to zero in on their own unique message, tell persuasive stories, and ultimately get their messages not only clearly heard but acted upon in a culturally diverse global business environment. Filled with lessons and real-life stories from global companies and executives who benefited from Natsuyo's guidance, this book will appeal to any business leader who needs to communicate with a diverse range of stakeholders, whether in a different country or a different team, to persuade and succeed.
Why isn't it getting through? -- Focus on one big message -- Present and captivate your global audience -- Communicate to transform your global team from good to great -- Make your message heard and acted upon in one-on-one communication -- Putting it all together, and the bonus A.
"Written by a non-native English-speaking professional speaker with over 20 years of international consulting experience, this book lays out a step-by-step process to improve cross-cultural communication skills and achieve a strong global presence. Every year organizations lose money, time, and people due to poor or inefficient cross-cultural communication-and this can be between departments or individuals within an organization as easily as across oceans. To tackle this widespread problem, Natsuyo Lipschutz developed the 3-step process she calls the "3 As" (Acknowledge, Analyze, Adapt), using a unique multi-layered approach: cross-culture X logical thinking X storytelling. Using the 3As process, readers will improve their awareness of cultural differences, learn analytical and logical thinking skills to zero in on their own unique message, tell persuasive stories, and ultimately, get their messages not only clearly heard but acted upon in a culturally diverse, global business environment. Filled with lessons and real-life stories from global companies and executives who benefitted from Natsuyo's guidance, this book will appeal to any business leader who needs to communicate with a diverse range of stakeholders, whether in a different country or a different team, to persuade and succeed"-- Provided by publisher.
Keywords: Intercultural communication; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Business Communication / Meetings & Presentations; BUSINESS & ECONOMICS / Development / Business Development